Mantle and Crustal Xenoliths in a Tephriphonolite From La Palma (Canary Islands): Implications for Phonolite Formation at Oceanic Island Volcanoes - Klügel, Andreas; Albers, Elmar; Hansteen, Thor H. (Frontiers in Earth Science, 2022)
Lavas from the active Cumbre Vieja volcano of La Palma (Canary Islands) are dominantly basanites to tephrites, but more evolved rocks are also common. A remarkable tephriphonolite lava with phonolitic groundmass composition contains abundant inclusions that represent the island's major xenolith types: kaersutite-dominated cumulates, gabbros from the oceanic crust, and peridotites from the mantle. Peridotite xenoliths in phonolitic melts are rarely observed worldwide, and on La Palma such xenoliths are usually confined to basanites. The peridotites are mantled by complex phlogopite-kaersutite-clinopyroxene-rich selvages, with adjacent up to 1.6 mm wide zonations where olivine changes its composition from Fo78-86 at the selvage contact to Fo89-91 inside the xenoliths. These features indicate prolonged contact of the peridotites with melts that were not in equilibrium with olivine. Diffusion calculations for Fe-Mg exchange show that this contact lasted decades to centuries, which is comparable to similar zonations in basanite-hosted peridotite xenoliths from Cumbre Vieja. Results from thermobarometry and hygrometry indicate that the tephriphonolite magma contained 3-4 wt.% H2O and was stored in the lower crust at around 250-350 MPa and 900-950 °C, at oxidized conditions (∆NNO of 2 to 3). Barometry data for other Cumbre Vieja tephriphonolites to phonolites give a similar pressure range. Our data thus document differentiation of evolved Cumbre Vieja melts in an inferred magma accumulation zone in the lowermost oceanic crust. The evolving melts receive periodic recharge from mantle-derived mafic magmas at intervals on the order of decades to a few centuries, comparable to historic eruption recurrences (80 years on average). Some of these recharge pulses carry mantle peridotite fragments that become part of a crystal mush in the accumulation zone. Thus, the occurrence of these xenoliths does not imply formation of the evolved melts in the mantle. A last mafic recharge likely triggered final ascent of the tephriphonolite some weeks before its eruption, resulting in entrainment and thorough mingling of a mixed xenolith population. We infer that the eruption of (tephri)phonolites at Cumbre Vieja indicates a mature state of the hot magma accumulation zone, such that rates and volumes of magma recharge pulses and of eruptive events are balanced.